2020
DOI: 10.1200/jop.19.00381
|View full text |Cite
|
Sign up to set email alerts
|

Impact of High-Quality Goals-of-Care Discussions on Oncologist Productivity

Abstract: PURPOSE: To study factors that have an impact on the conduct of high-quality goals of care (GoC) discussions and productivity of oncologists among four different practice settings in patients with advanced cancer. METHODS: Solid-tumor oncologists from community, academic, municipal, and rural hospitals were randomly assigned to receive a coaching model of communication skills to help them facilitate a GoC discussion with newly diagnosed patients with advanced cancer who had a less-than-2-year prognosis. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…However, it meets proposed best practices 26 and clinicians' desire for systematic integration into clinical care, 45 and data suggest that high-quality GOC discussions need not be lengthy 46 and do not affect oncologist productivity. 47 The templated note we implemented was designed by an interdisciplinary group of clinicians with the aim of being brief, user-friendly, and accommodating of clinical team workflows. Additional implementation efforts could be expected to improve performance, which we will continue to study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it meets proposed best practices 26 and clinicians' desire for systematic integration into clinical care, 45 and data suggest that high-quality GOC discussions need not be lengthy 46 and do not affect oncologist productivity. 47 The templated note we implemented was designed by an interdisciplinary group of clinicians with the aim of being brief, user-friendly, and accommodating of clinical team workflows. Additional implementation efforts could be expected to improve performance, which we will continue to study.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, we did not survey clinicians' attitudes about our GOC documentation initiative, including perceived benefits or burdens. However, it meets proposed best practices 26 and clinicians' desire for systematic integration into clinical care, 45 and data suggest that high‐quality GOC discussions need not be lengthy 46 and do not affect oncologist productivity 47 . The templated note we implemented was designed by an interdisciplinary group of clinicians with the aim of being brief, user‐friendly, and accommodating of clinical team workflows.…”
Section: Discussionmentioning
confidence: 99%
“…38 Data also exist that stand in contrast to some of these perceived barriers, including a study that identified no difference in hope among patients with advanced cancer who had completed ACP, 39 and another that identified no difference in productivity among oncologists who performed high-quality GoC discussions. 40 ASCO's recent Patient-Clinician Communication guidelines emphasize early GoC discussions as a key target of effective communication in the setting of palliative cancer, citing evidence that these discussions can support the well-being of patients, families, and clinicians. 1 However, the belief that increasing the frequency of GoC designation is a suitable target for quality improvement is not universal.…”
Section: Discussionmentioning
confidence: 99%
“…38 Data also exist that stand in contrast to some of these perceived barriers, including a study that identified no difference in hope among patients with advanced cancer who had completed ACP, 39 and another that identified no difference in productivity among oncologists who performed high-quality GoC discussions. 40…”
Section: Discussionmentioning
confidence: 99%